2023
DOI: 10.1093/gerona/glad007
|View full text |Cite
|
Sign up to set email alerts
|

X Chromosome Factor Kdm6a Enhances Cognition Independent of Its Demethylase Function in the Aging XY Male Brain

Abstract: Males exhibit shorter lifespan and more cognitive deficits, in the absence of dementia, in aging human populations. In mammals, the X chromosome is enriched for neural genes and is a major source of biologic sex difference, in part, because males show decreased expression of select X factors (XY). While each sex (XX and XY) harbors one active X due to X chromosome inactivation in females, some genes, such as Kdm6a, transcriptionally escape silencing in females – resulting in lower transcript levels in males. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
(46 reference statements)
0
6
0
Order By: Relevance
“… 68 The expression of the XCI escapee gene, Kdm6a, in males has beneficial effects on cognitive aging. 69 Thus, X chromosomal hermaphroditic bias in gene expression may be a conserved feature, and these biased genes may act to regulate cognitive health with age in hermaphrodites and females. Together, our analyses uncovered genes and pathways that may affect neuronal aging in a sex-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“… 68 The expression of the XCI escapee gene, Kdm6a, in males has beneficial effects on cognitive aging. 69 Thus, X chromosomal hermaphroditic bias in gene expression may be a conserved feature, and these biased genes may act to regulate cognitive health with age in hermaphrodites and females. Together, our analyses uncovered genes and pathways that may affect neuronal aging in a sex-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in mammals, histone modification enzymes are also among the X chromosomal inactivation (XCI) escapee genes that are found to be expressed from the inactivated X chromosome (Berletch et al, 2010). The expression of the XCI escapee gene, Kdm6a, in males has beneficial effects on cognitive aging (Shaw et al, 2023). Thus, X chromosomal hermaphroditic bias in gene expression may be a conserved feature, and these biased genes may act to regulate cognitive health with age in hermaphrodites and females.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we reduced expression of a small set of highly-upregulated candidate genes in categories that might function in a compensatory manner. These include utx-1, a histone demethylase known to play a role in development 38 and lifespan in worms [39][40][41] , and whose homolog has been implicated in cognition in mammals 42,43 ; ins-19, an insulin-like peptide; and nmgp-1, a neuronal glycoprotein involved in chemosensation 44 . In each case, we see that gene expression is significantly higher in old than in young neurons (Fig.…”
Section: Wild-type Neurons Lose Their Neuronal Function and Identity ...mentioning
confidence: 99%
“…We hypothesized that genes that are expressed at higher levels in aged neurons might be harmful to neurons, and therefore reducing their expression might be beneficial to the worm. To investigate this hypothesis, we tested the candidates utx-1 (a histone demethylase known to play a role in development 30 and lifespan in worms [31][32][33] , whose homolog has been implicated in cognition in mammals 34,35 ), ins-19, an insulin-like peptide, and nmgp-1, a neuronal glycoprotein involved in chemosensation 36 (Figure 3C, E, G). We found that adult-only knockdown of utx-1 increases 1hr and 2hr memory (Figure 3D), mutation of ins-19 increases both learning and memory (Figure 3F).…”
Section: Neurons Lose Their Neuronal Function and Identity With Agementioning
confidence: 99%